Decision factors of air cargo freight forwarders for transport service providers in different geographic regions: a systematic literature review - de Haan, Floris; Mayer, Robert; Uyan, Berkcan (Elsevier, 2026)
Air cargo transportation facilitates companies in global supply chains in organising production on different continents. High value and perishable goods make extensive use of air cargo as preferred mode of transport. Shippers typically outsource their transportation needs to freight forwarding companies with extensive expertise and global presence. The air cargo industry remains relatively underexplored academically and little is known about the decision making of freight forwarding companies in selecting air transport service providers such as airlines, airports and trucking companies. While existing research investigates Asian exports, there is lack of research from the past 25 years on the distinct European market context. This paper aims to review the literature that is available in the field of decision making at air cargo freight forwarding companies and synthesises the outcomes. The paper also identifies that there is no literature available on freight forwarding companies selecting trucking companies that provide pick-up services at the shipper as part of the air transport chain. Finally, continuation of research is proposed in the field of decision making at European based freight forwarding companies exporting air cargo shipments from Europe.
Keywords: 3509 Transportation, Logistics and Supply Chains; 35 Commerce, Management, Tourism and Services; 3509 Transportation, logistics and supply chains; Air cargo; decision making; freight forwarding